2023
DOI: 10.1152/japplphysiol.00748.2022
|View full text |Cite
|
Sign up to set email alerts
|

Soluble RAGE and skeletal muscle tissue RAGE expression profiles in lean and obese young adults across differential aerobic exercise intensities

Edwin R. Miranda,
Jacob T. Mey,
Brian K. Blackburn
et al.

Abstract: Nearly 40% of Americans have obesity and are at increased risk for developing type 2 diabetes. Skeletal muscle is responsible for >80% of insulin-stimulated glucose uptake which is attenuated by the inflammatory milieu of obesity and augmented by exercise. The Receptor for Advanced Glycation Endproducts (RAGE) is an inflammatory receptor directly linking metabolic dysfunction with inflammation. Circulating soluble isoforms of RAGE (sRAGE) formed either by proteolytic cleavage (cRAGE) or alternative splicing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 91 publications
0
1
1
Order By: Relevance
“…To our knowledge, this is the first report on circulating sTLR and sRAGE levels in individuals with apparent abnormal glucose regulation following acute aerobic exercise. However, we recently demonstrated that while young individuals with obesity have higher muscle RAGE protein expression, they do not appear to exhibit different circulating sRAGE levels (Miranda et al, 2023). Furthermore, muscle RAGE expression was strongly related to HOMA-IR, in disagreement with findings presented here.…”
Section: Select Relationships Among Independent Variables and Primary...contrasting
confidence: 97%
“…To our knowledge, this is the first report on circulating sTLR and sRAGE levels in individuals with apparent abnormal glucose regulation following acute aerobic exercise. However, we recently demonstrated that while young individuals with obesity have higher muscle RAGE protein expression, they do not appear to exhibit different circulating sRAGE levels (Miranda et al, 2023). Furthermore, muscle RAGE expression was strongly related to HOMA-IR, in disagreement with findings presented here.…”
Section: Select Relationships Among Independent Variables and Primary...contrasting
confidence: 97%
“…It is worthy of note that bulk RNA-seq can have some pitfalls when the heterogeneity of the tissues is high (Denninger, et al 2022; Li and Wang 2021; Noureen, et al 2022). An expansion of adipose tissue due to HFD exposure has been shown not only to change the cell profile in adipose tissue by increasing proinflammatory cells, but also in skeletal muscle (Chait and den Hartigh 2020; Fuster, et al 2016; Miranda, et al 2023; Morgan, et al 2020).…”
Section: Discussionmentioning
confidence: 99%